2022
DOI: 10.1016/j.jvs.2021.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the literature and standards of reporting on stroke after carotid revascularization

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The 6 patients who displayed a postoperative ischemic event developed a non-disabling minor stroke or transient ischemic attack. The overall rate in our cohort of patients was 8.8% which is consistent with the incidence of ischemic events of 10.2% following CEA reported in the literature ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…The 6 patients who displayed a postoperative ischemic event developed a non-disabling minor stroke or transient ischemic attack. The overall rate in our cohort of patients was 8.8% which is consistent with the incidence of ischemic events of 10.2% following CEA reported in the literature ( 16 , 17 ).…”
Section: Discussionsupporting
confidence: 91%
“…This classification is based on few clinical variables: time of the event after the carotid procedure, affected brain territory, and severity of the ischemic event. (15) Knowing the real incidence of this event through a compulsory notification may be the best way to improve patient outcomes, especially with the implementation of protocols for early recognition and intervention. (16) Studies on amputations after revascularization for PAD have reported that amputation rates after lower limb revascularization procedures vary between 0 and 7%.…”
Section: Stroke After Carotid Revascularizationmentioning
confidence: 99%
“…The definition of perioperative stroke is the following: any embolic, thrombotic, or hemorrhagic cerebrovascular event with motor, sensory, or cognitive dysfunction lasting at least 24 h, occurring intraoperatively or within 30 days after surgery [18]. However, the risk of perioperative neurological events most frequently arises from diminished cerebrovascular reserve capacity, typically resulting in hypoperfusion-induced ischemia or procedural factors, rather than embolization linked to plaque-related mechanisms [19]. In our review, we focus on the risk assessment of perioperative neurological events caused by impaired cerebrovascular reserve capacity in patients with asymptomatic carotid artery stenosis.…”
Section: Introductionmentioning
confidence: 99%